Some Priority Challenges of the Nursing Sector in India - Raha, Shomikho; Berman, Peter; Bhatnagar, Aarushi (World Bank, Washington, DC, 2013)
This note identifies some key areas for priority action in the current favorable contest for policy in the nursing sector in India. The present policy focus on increasing the number of nurses and nurse training centers is understandable given the countries nurse-to-population ratio is very low. However; based on evidence from Uttar Pradesh and Tamil Nadu, the findings presented here suggest that such a focus on numbers alone are not the priority concerns of nursing.